Characterizing Croatian Wheat Germplasm Diversity and Structure in a European Context by DArT Markers - Novoselović, Dario; Bentley, Alison R.; Šimek, Ruđer; Dvojković, Krešimir; Sorrells, Mark E.; Gosman, Nicolas; Horsnell, Richard; Drezner, Georg; Šatović, Zlatko (Frontiers in Plant Science, 2016)
Narrowing the genetic base available for future genetic progress is a major concern to plant breeders. In order to avoid this, strategies to characterise and protect genetic diversity in regional breeding pools are required. In this study, 89 winter wheat cultivars released in Croatia between 1936 and 2006 were genotyped using 1,229 DArT (Diversity Array Technology) markers to assess the diversity and population structure. In order to place Croatian breeding pool in a European context, Croatian wheat cultivars were compared to 523 European cultivars from seven countries using a total of 166 common DArT markers. The results show higher genetic diversity in the wheat breeding pool from Central Europe (CE) as compared to that from Northern and Western European (NWE) countries. The most of the genetic diversity was attributable to the differences among cultivars within countries. When the geographical criterion (CE vs. NWE) was applied, highly significant difference between regions was obtained that accounted for 16.19 % of the total variance, revealing that the Croatian breeding pool represents genetic variation not currently captured in elite European wheat. The current study emphasises the important contribution made by plant breeders to maintaining wheat genetic diversity and suggests that regional breeding is essential to the maintenance of this diversity. The usefulness of open-access wheat datasets is also highlighted.